Effect of Globalization on Economic Development: The Nigerian Perspective - Bernadine Ikwuagwu, Eberechi; Ugwuanyi, Wilfred; Onyekachi Onyele, Kingsley (Disclosure: Journal of Accounting and Finance, 2025)
The study is an empirical investigation of the effect of globalisation on economic development in Nigeria. This emanates from the problem that globalisation is a broad concept and mechanism with its strengths, weaknesses, opportunities, and threats. The objectives of the study were to determine the effect of the globalisation index, capital inflows, the volatility index, and the exchange rate on gross domestic product per capita in Nigeria. Being empirical research with historical data, the ex post facto research design was used with data spanning from 1986 to 2022. On this basis, the Autoregressive Distributed Lag (ARDL) approach was adopted since the unit root test results showed that the data were of mixed integration. The ARDL bounds test for cointegration revealed evidence of long-run relationships across the models developed for the study. The long-run estimates showed that globalisation had a positive and significant effect on GDP per capita. The study concluded that globalisation enhanced GDP per capita in Nigeria. The recommendations were a robust and effective economic environment that would seize opportunities from the current globalisation wave to ensure improvements in the domestic industries to achieve the desired level of economic development in Nigeria.